2009
DOI: 10.1111/j.1751-9020.2008.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Beauty Work: Individual and Institutional Rewards, the Reproduction of Gender, and Questions of Agency

Abstract: Physical attractiveness is associated with a number of positive outcomes, including employment benefits such as hiring, wages, and promotion, and is correlated with social and personal rewards such as work satisfaction, positive perceptions of others, and higher self‐esteem. As a result, individuals perform various forms of beauty work, thus reproducing and strengthening a social system that privileges youth and attractiveness. In this article, we explore the beauty work practices that people perform. We begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 94 publications
0
89
0
Order By: Relevance
“…Like Melissa, Marilyn agreed with the notion of social conditioning for women to compete amongst each other rather than to exclusively impress men, even though they are ultimately judging themselves according to standards that in part reflect a male gaze [30]. For instance, ongoing educational and outreach programs highlight manifestations of ''involuntary internalization'' of sexism include ''self-doubt…-self-censorship, plus doubt or mistrust of and competition with other women'' [9], along with the process of blaming and disliking themselves or other women [40].…”
Section: Competitionmentioning
confidence: 73%
See 2 more Smart Citations
“…Like Melissa, Marilyn agreed with the notion of social conditioning for women to compete amongst each other rather than to exclusively impress men, even though they are ultimately judging themselves according to standards that in part reflect a male gaze [30]. For instance, ongoing educational and outreach programs highlight manifestations of ''involuntary internalization'' of sexism include ''self-doubt…-self-censorship, plus doubt or mistrust of and competition with other women'' [9], along with the process of blaming and disliking themselves or other women [40].…”
Section: Competitionmentioning
confidence: 73%
“…For instance, even when women know images are digitally altered and therefore unrealistic, they still believe these images universally reflect men's, and their significant others', preferences [5]. These comparisons may be taken a step further through reflected appraisals, consisting of individuals imposing other peoples' appraisals of an individual onto themselves [18,30]. For instance, Milkie [34] found that young women remained critical of unrealistic images of femininity in the media, yet White women particularly experienced lowered self-esteem; this occurred because they thought others, and especially men, used or viewed idealized images as an important measurement for evaluating them as women.…”
Section: Feminine Ideals and Social Comparisonmentioning
confidence: 97%
See 1 more Smart Citation
“…One reason for women to wear makeup is to increase their perceived competence and credibility [Kwan and Trautner, 2009]. In other cases, the goal of applying makeup is to make a subject look younger, while in the case of young subjects the opposite effect might be desired [Kwan and Trautner, 2009]. Here, we seek to observe the impact of makeup on an automated age estimation algorithm.…”
Section: Makeup Induced Age Alterationmentioning
confidence: 99%
“…This is accomplished by concealing wrinkles and age spots (using light foundation and a concealer), by brightening wrinkle-induced shadows in eye, nose and mouth regions (using concealer and powder), and by highlighting and coloring cheeks (using highlighter and blush). One reason for women to wear makeup is to increase their perceived competence and credibility [Kwan and Trautner, 2009]. In other cases, the goal of applying makeup is to make a subject look younger, while in the case of young subjects the opposite effect might be desired [Kwan and Trautner, 2009].…”
Section: Makeup Induced Age Alterationmentioning
confidence: 99%